Learning to read facilitates the retrieval of phonological representations in rapid automatized naming: Evidence from unschooled illiterate, ex‐illiterate, and schooled literate adults. Issue 4 (18th January 2019) - Araújo, Susana; Fernandes, Tânia; Huettig, Falk
Abstract: Rapid automatized naming (RAN) of visual items is a powerful predictor of reading skills. However, the direction and locus of the association between RAN and reading is still largely unclear. Here, we investigated whether literacy acquisition directly bolsters RAN efficiency for objects, adopting a strong methodological design, by testing three groups of adults matched in age and socioeconomic variables, who differed only in literacy/schooling: unschooled illiterate and ex‐illiterate, and schooled literate adults. To investigate in a fine‐grained manner whether and how literacy facilitates lexical retrieval, we orthogonally manipulated the word‐form frequency (high vs. low) and phonological neighborhood density (dense vs. spare) of the objects' names. We observed that literacy experience enhances the automaticity with which visual stimuli (e.g., objects) can be retrieved and named: relative to readers (ex‐illiterate and literate), illiterate adults performed worse on RAN. Crucially, the group difference was exacerbated and significant only for those items that were of low frequency and from sparse neighborhoods. These results thus suggest that, regardless of schooling and age at which literacy was acquired, learning to read facilitates the access to and retrieval of phonological representations, especially of difficult lexical items. Abstract : Literacy acquisition and experience assists faster access to phonological lexical representations of hard items (i.e., words with low‐frequency or from sparse neighborhoods), possibly through support provided by orthographic knowledge.